Enhanced Of Phagocyte Activity Of Nile (Oreochromis niloticus) Macrophage After Administered With Pseudomonas sp Formalin-Killed Cells And Lipopolysaccharide Ofthe Bacterium - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT Suprapto, H. 2004. Enhanced of Phagocyte Activity of Nile (Oreochromis niloticus) Macro-phage After Administered With Pseudomonas sp Formalin-Killed Cells and Lypopolysaccharide of The Bacterium. Biologi 3 (4): 257- 265. Pseudomonas sp. infection was one of the main problems of the Nile culture in Indonesia. Experiment to enhance the phagocyte activity of Nile macrophage by administration of antigen deriving from Pseudomonas sp was conducted. The survival rate (SR) of Niles injected with 10 mg/fish and 15 mg/fish of Formalin-Killed Cells (FKC) were 70% and 60%, respectively. The injected fish with 0.50 ml/fish and 0.75 ml/ fish of Lipopolysaccharide (LPS) showed similar SR, 60%. The SR was followed by the increase of phagocytes activity of macrophage in both vaccination with FKC (8.0) and LPS (7.0). Antibody titer of vaccinated fish reached the highest titer after 14 days of antigen administration. The antibody titer for FKC treatment was 1.984 while LPS treatment was 1.024. The results showed that the average protection of fish administered with both FKC and LPS treatment were higher than the controlled fish.